Chemoenzymatic total synthesis of nodulones C and D using a naphthol reductase of Magnaporthe grisea. Issue 18 (25th April 2022) - Manna, Tanaya; Rajput, Anshul; Saha, Nirmal; Mondal, Amit; Debnath, Subhas Chandra; Husain, Syed Masood
Abstract : Herein, the asymmetric and chemoenzymatic synthesis of ( R )-nodulone C, cis -nodulone D and related ( R )-dihydronaphthalenone is reported. Abstract : Herein, the asymmetric and chemoenzymatic synthesis of ( R )-nodulone C, cis -nodulone D and related ( R )-dihydronaphthalenone is reported. It involves multistep chemical synthesis of putative biosynthetic substrates followed by regio- and stereoselective reduction using a NADPH-dependent tetrahydroxynaphthalene reductase of Magnaporthe grisea to obtain chiral nodulones in a biomimetic fashion.